The morphological evolution of -ile suffix across Bantu languages : The case of Nyasa-Tanganyika corridor (JULACE: Journal of the University of Namibia Language Centre, 2022)
This paper describes morphological properties of -ile suffix across four Bantu languages selected from the Nyasa-Tanganyika corridor. The suffix -ile which is traditionally an aspect (perfective) marker is changing and becoming amenable to different roles across Bantu languages. The changing behaviour of the suffix and/or its disappearance in some languages makes it difficult to specify its roles unless close attention is paid to an individual language. The findings presented in this paper indicate that in the languages under study, the suffix –ile functions as both a tense and an aspect marker. It co-occurs with pre-root formatives to mark different past tenses. In Nyakyusa, in particular, the suffix marks different categories of aspect, namely anterior, non-progressive and indefinite conditional aspect. However, in Ndali, Malila and Nyiha, the suffix -ile marks only the non-progressive aspect. The data examined in this paper indicate that the additional role of -ile suffix has changed in addition to its traditional role, i.e., marking aspect; the suffix marks tense categories as well.
Keywords: Morphological evolution, -ile suffix, tense, aspect, Nyasa-Tanganyika corridor